2009
DOI: 10.1093/schbul/sbp058
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampi, Thalami, and Accumbens Microstructural Damage in Schizophrenia: A Volumetry, Diffusivity, and Neuropsychological Study

Abstract: Volumetric abnormalities in the subcortical structures have been described in schizophrenia. However, it still has to be clarified if subtle microstructural damage is also present. Thus, we aimed to detect subcortical volume and mean diffusivity (MD) alterations in 45 patients with diagnosis of schizophrenia compared with 45 age-, gender-, and educational attainment-matched healthy comparison (HC) participants, by using a combined volumetry and diffusion tensor imaging (DTI) method. A secondary aim was to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
40
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 66 publications
8
40
0
Order By: Relevance
“…The negative relationship between right hippocampus and working memory in the combined group is substantiated by previously reported findings in bipolar disorder (Ali et al, 2000) as well as in schizophrenia (Spoletini et al, 2011). Furthermore, functional MRI studies have shown hippocampal activity during working memory tasks in healthy individuals , suggesting hippocampal involvement in short-term memory networks as well as in long-term memory networks.…”
Section: Discussionsupporting
confidence: 78%
“…The negative relationship between right hippocampus and working memory in the combined group is substantiated by previously reported findings in bipolar disorder (Ali et al, 2000) as well as in schizophrenia (Spoletini et al, 2011). Furthermore, functional MRI studies have shown hippocampal activity during working memory tasks in healthy individuals , suggesting hippocampal involvement in short-term memory networks as well as in long-term memory networks.…”
Section: Discussionsupporting
confidence: 78%
“…This is not the first study pointing to altered diffusion parameters in the thalamus or thalamocortical pathways. DTI findings supporting altered integrity of thalamocortical connectivity in schizophrenia include controversial alterations of fractional anisotropy in the anterior limb of the internal capsule (ALIC) Kubicki et al, 2005;Mamah et al, 2010;Sprooten et al, 2009;Sussmann et al, 2009;Zhang et al, 2010;Zhou et al, 2008, but see Ashtari et al, 2007;Kito et al, 2009;Kyriakopoulos et al, 2008;Szeszko et al, 2005;White et al, 2007 for negative findings in younger individuals and Beasley et al, 2009 for lack of evidence of myelin abnormalities post-mortem), of the tracts connecting to the LPFC (Kim et al, 2008;Oh et al, 2009) and altered FA (Hashimoto et al, 2009) or mean diffusivity in the thalamus itself (Agarwal et al, 2008;Rose et al, 2006;Spoletini et al, 2011). Kim et al (2007) have performed a similar DTI study, with an identical a-priori hypothesis, but found only differences in the thalamic CDR defined by connectivity to the orbitofrontal, parietal, and medial prefrontal cortices.…”
Section: Discussionmentioning
confidence: 99%
“…Our group recently demonstrated that patients with schizophrenia have relatively disturbed lexico-semantic processing and are less informative and more tangential than healthy controls (Marini et al, 2008). There is evidence that patients with schizophrenia are characterized by structural abnormalities in subcortical brain areas, such as the hippocampus (Kalus et al, 2004), amygdala (Meisenzahl et al, 2008), thalamus (Rose et al, 2006), caudate, putamen, and accumbens (Spoletini et al, 2009), as well as in cortical areas such as fronto-temporal regions (Honea et al, 2005). These structures have also been reported as playing a crucial role in language processing (e.g.…”
Section: Introductionmentioning
confidence: 99%